2020
DOI: 10.3389/fspor.2020.00041
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Preconditioning Enhances Aerobic Adaptations to Sprint-Interval Training in Athletes Without Altering Systemic Hypoxic Signaling and Immune Function

Abstract: Optimizing traditional training methods to elicit greater adaptations is paramount for athletes. Ischemic preconditioning (IPC) can improve maximal exercise capacity and up-regulate signaling pathways involved in physiological training adaptations. However, data on the chronic use of IPC are scarce and its impact on high-intensity training is still unknown. We investigated the benefits of adding IPC to sprint-interval training (SIT) on performance and physiological adaptations of endurance athletes. In a rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 60 publications
(34 reference statements)
1
32
0
Order By: Relevance
“…Paradis-Deschênes et al ( 2020 ) reported that IPC combined with sprint-interval training throughout 4 weeks (2 days/weeks) increased exercise performance and its-related parameters during 5-km time trial (e.g., completion time) and 30-s Wingate test (e.g., fatigue index) more than those of placebo intervention (i.e., training alone) in endurance athletes. They also determined positive effects of the IPC intervention on perfusion and metabolic changes (e.g., changes in deoxy-hemoglobin/myoglobin) of the exercising muscle during these whole-body exercises (Paradis-Deschênes et al, 2020 ). Additionally, Carvalho et al ( 2020 ) reported that IPC combined with knee extensor resistance training throughout 6 weeks (2 days/week) increased the knee extensor one-repetition maximum more than the placebo intervention in resistance-trained individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Paradis-Deschênes et al ( 2020 ) reported that IPC combined with sprint-interval training throughout 4 weeks (2 days/weeks) increased exercise performance and its-related parameters during 5-km time trial (e.g., completion time) and 30-s Wingate test (e.g., fatigue index) more than those of placebo intervention (i.e., training alone) in endurance athletes. They also determined positive effects of the IPC intervention on perfusion and metabolic changes (e.g., changes in deoxy-hemoglobin/myoglobin) of the exercising muscle during these whole-body exercises (Paradis-Deschênes et al, 2020 ). Additionally, Carvalho et al ( 2020 ) reported that IPC combined with knee extensor resistance training throughout 6 weeks (2 days/week) increased the knee extensor one-repetition maximum more than the placebo intervention in resistance-trained individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Most reports to date have conducted their exercise testing acutely on the same day as the IPC stimulus. However, a minority of studies have conducted exercise testing after repeated daily IPC exposure ranging from 7 days to 6 weeks (Banks et al, 2016 ; Jeffries et al, 2019 ; Slysz and Burr, 2019 ; Mieszkowski et al, 2020 ; Paradis-Deschênes et al, 2020a ; Surkar et al, 2020 ). There also is substantial variation in whether IPC is administered unilaterally or bilaterally to the limb(s), which may influence the magnitude of response.…”
Section: Methodological Variations Contributing To Heterogeneous Responsesmentioning
confidence: 99%
“…The evidence that central humoral, neural, and systemic ischemic protection mediate IPC benefits suggests that the location of the application of IPC may not have an optimal site of application. Alternatively, muscle deoxygenation responses during exercise preceded by local (Paradis-Deschênes et al, 2016 , 2020a ), but not always remote IPC (Barbosa et al, 2015 ), may suggest that the IPC stimulus is optimized when administered in close proximity to the exercising tissues. Without a comprehensive understanding of the mechanisms most likely to elicit an ergogenic response, it is difficult to determine if there are advantages favoring remote or local IPC in terms of the probability of an ergogenic effect.…”
Section: Methodological Variations Contributing To Heterogeneous Responsesmentioning
confidence: 99%
“…This investigation was part of a larger project examining the impact of IPC on endurance performance adaptations and blood markers of angiogenesis and hypoxic signaling. These data have been published elsewhere [ 13 ]. Since short-term endurance performance can also be influenced by anaerobic capacity, we also investigated the effects of training with IPC on this endurance performance determinant and the concurrent neuromuscular function changes.…”
Section: Methodsmentioning
confidence: 99%
“…IPC used prior to high-intensity training sessions (tempo runs) for 8 weeks failed to enhance VO 2 max and 1-km time-trial running performance in distance runners compared to the same training with placebo compressions [ 9 ]. On the other hand, our laboratory reported ergogenic effects of 4 weeks of IPC applied before sprint-interval training (SIT) sessions on 5-km cycling time-trial performance in endurance athletes [ 13 ]. The discrepancy in these conclusions may be due to the different IPC procedures (unilateral vs. bilateral), probably inducing a different vascular/metabolic cascade and the intensity of the training sessions (tempo vs. “all-out” efforts).…”
Section: Introductionmentioning
confidence: 99%